Age, growth, and gonadal condition of the Giant mottled eel, Anguilla marmorata, in Okinawa-Jima Island, Japan - Kita, Tomohiro; Tachihara, Katsunori (Environmental biology of fishes, 2020)
Age, growth, and gonadal condition of the Giant mottled eel, Anguilla marmorata , were estimated from 303 specimens collected at Okinawa-jima Island, Japan. Otolith opaque zones that formed every year correlated with high water temperature and were thought to be annual rings. The growth of this species differed between males and females, and females were longer lived and larger than males. The mean gonadosomatic index (GSI) and the appearance of silver eels showed no clear seasonality. Comparing life history characteristics of this species between natural (northern specimens) and urban rivers (southern specimens), the growth of southern specimens was faster than that of the northern specimens, leading to the development of gonads and their downstream migration at younger ages. Therefore, we conclude that the life history characteristics of A. marmorata strongly influence by the river environments.